Kesesuaian Kompetensi Profesional Guru Kecantikan Sekolah Menengah Kejuruan dengan Standar Industri di Malang: Studi Kualitatif - Mutiara Arafa Camila; Nunung Nurjanah; Didik Nurhadi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The rapid development of the beauty industry requires vocational education institutions, particularly Beauty Vocational High Schools, to produce graduates who are not only technically skilled but also adaptable to the dynamics of the job market. However, many vocational school graduates are considered unprepared for work, raising questions about the relevance of the curriculum, teacher competence, and alignment with industry needs. This study aims to evaluate the curriculum standards of Beauty Vocational High Schools in Malang Raya, assess teachers' professional competencies, and explore industry expectations for vocational graduates. The results indicate that the curriculum remains focused on basic techniques and has not incorporated modern makeup trends, small business management, and the use of digital media. Teachers' competencies are also suboptimal due to limited industry training, resulting in teaching methods that are conventional and lack contextual relevance. The industry expects graduates who are ready to work, communicative, and able to promote services independently. The gap between school learning and field practice underscores the need for closer collaboration between schools and the workplace. The implications of these findings emphasize the importance of curriculum updates, enhancing teacher capacity through industry training, and strengthening Teaching Factories to improve graduate competitiveness.